Understanding unsuccessful attempts to quit smoking: a social phenomenology approach - Maria Cristina Pinto de Jesus; Marcelo Henrique da Silva; Samara Macedo Cordeiro; Estela Kortchmar; Vanderleia Soeli de Barros Zampier; Miriam Aparecida Barbosa Merighi (SciELO, 2016)
Abstract OBJECTIVE The aim of this paper is to understand the experience of smokers in view of unsuccessful attempts to quit smoking. METHOD This study is based on social phenomenology. Between November and December of 2014, nine interviews were conducted with people that had attempted to quit smoking. The content of these interviews was analyzed and discussed based on the related literature. RESULTS Unsuccessful attempts to quit smoking are related to tobacco addiction; cigarettes are seen as a support to cope with everyday stressful situations. Attempts to quit the smoking habits were based on the need of health improvement and insistence of family and friends. Smokers reported the use of habit cessation strategies learned in support groups, but they also express expectation of specialized psychological support. CONCLUSION The study points out the need to expand the strategies of approaching smokers, and reinforcing psychological support in order to achieve success in the attempt to quit smoking.